Developing and assessing shape grammar design systems - Eloy, S.; Andrade, M.; Lopes, P. F. (Winter School 2018 ISTAR-IUL Applied Transdisciplinary Research, 2018)
The ongoing and future research focus on the developing and assessing shape grammars design systems for architecture. The work started by the join paper from Eloy (ISTAR-IUL), Vermaas (TU Delft) and Andrade (ISTAR-IUL) (Eloy, Vermaas, & Andrade, n.d.) where the quality of designs generated by shape grammar systems with designs created by professional architects was compared. In this work authors collaborated in defining and analysing an experiment in which evaluators rank the quality of preliminary designs for refurbishing Lisbon’s Rabo-de-Bacalhau apartments, and that makes plausible that the design quality of the grammar solutions for this task is similar to that of the designs of the professional architects. It was argued that shape grammars can therefore be used as stand - alone design systems in architecture. The practical value is that shape grammar systems become alternative means to take up design challenges (such as refurbishing all of Lisbon’s Rabo -de-Bacalhau apartments) that currently require too much effort of architects to be economically feasible. In the scope of the developed work the three authors joined a consortium composed by TU Ghent, ISCTE-IUL, TU Delft, SWAP, MVRDV, ARUP and Caramel for a call proposal to H202 0 ICT-20-2017. The proposal project aims at bringing out creative architectural design content as smart digital data, and making this data effectively re - usable across different use - cases, offices and purposes. The project shall create a design engine that can work with given datasets and shape grammar rule set s to generate diverse alternative design solutions. The designs generated by the engine are customized since they responds to specifically selected architectural design language, to building regulations and to a particular architectural design brief. In this H2020 proposal the team of ISCTE-IUL was composed by Eloy, Andrade and Lopes. Within the project workplan the task and collaboration between the ISTAR group was the following: Sara Eloy tasks were related to architectural design and shape grammar design rules definition, Pedro Faria Lopes collaborated on the interface design and tests, Marina Andrade was part of the team for developing the experimental settings and performing statistical analysis.